2002
DOI: 10.1128/aac.46.9.3057-3060.2002
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropenamide Derivatives AT-61 and AT-130 Inhibit Replication of Wild-Type and Lamivudine-Resistant Strains of Hepatitis B Virus In Vitro

Abstract: The phenylpropenamide derivatives AT-61 and AT-130 are nonnucleoside analogue inhibitors of hepatitis B virus (HBV) replication. They inhibited the replication of wild-type HBV with 50% inhibitory concentrations of 21.2 ؎ 9.5 and 2.40 ؎ 0.92 M, respectively, compared to 0.064 ؎ 0.020 M lamivudine. There were no significant differences in sensitivity between wild-type and nucleoside analogue-resistant (rtL180M, rtM204I, and rtL180M ؉ rtM204V) HBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 33 publications
0
118
0
Order By: Relevance
“…For instance, in the case of hepatitis B virus (HBV), several inhibitors targeting the core protein have been reported, and at least two classes of HBV assembly effectors, the heteroaryldihydropyrimidines (HAPs) and phenylpropenamides, have been extensively characterized (53,54,55,56). For the HAPs, elegant work from Zlotnick and colleagues demonstrated that these compounds can increase the kinetics of assembly and strengthen dimer-dimer association to stabilize capsids (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the case of hepatitis B virus (HBV), several inhibitors targeting the core protein have been reported, and at least two classes of HBV assembly effectors, the heteroaryldihydropyrimidines (HAPs) and phenylpropenamides, have been extensively characterized (53,54,55,56). For the HAPs, elegant work from Zlotnick and colleagues demonstrated that these compounds can increase the kinetics of assembly and strengthen dimer-dimer association to stabilize capsids (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…AEfs such as HAPs and phenylpropenamides have been suggested as antiviral agents (18,19,27,44). A caveat to their use as therapy would be the emergence of resistant mutants.…”
Section: Discussionmentioning
confidence: 99%
“…These includes myristilated pre-S1 peptides to compete with the interaction of the virion envelope proteins and the hepatocyte receptor , peptides or recombinant core proteins exhibiting a trans dominant negative effect on nucleocapsid assembly (von Weizsacker et al, 1999), non nucleosides inhibitors that inhibit the correct assembly and packaging of pregenomic RNA, iminosugars to inhibit the correct glycosylation process of viral envelope proteins and the maturation of virions. For instance, phenylpropenamide derivatives were shown to inhibit HBV replication independently of an interference with the viral polymerase activity (Delaney et al, 2002;King et al, 1998). It was suggested that these compounds may inhibit the packaging of pregenomic RNA, which in turn may explain their antiviral activity on both wild type and lamivudine resistant strains.…”
Section: Perspectivementioning
confidence: 99%